A situation analysis on scheduling nursing personnel during the COVID-19 outbreak (抗击新型冠状病毒肺炎疫情护理排班态势分析) - ZHANG Xiumei (张秀梅); HAN Qiuying (韩秋英); ZHANG Suzhen (张素真) (中西医结合护理)
To analyze the potential problems in scheduling nursing personnel in different periods of the COVID-19 Outbreak by using a situation analysis method, and to provide clinical practice for nursing staff to schedule major public health emergencies in the future. In the early stage, nursing staff were shifted according to the proportion, the grouping and partitioning were arranged in the mid-term, and number of staff was reduced to a reasonable shift in the later stage. (应用态势分析法对抗击新型冠状病毒肺炎疫情护理人员面临的内外问题进行分析, 并以此为依据在相应时期采用相应的排班方法, 早期按比例抽人排班, 中期编组、分区分岗排班, 后期逐渐减员, 减轻护理人员工作负荷。)